Isocinetisme et sport de haut niveau : Applications à la traumatologie du sport - Barthélémy, Y.; Kaux, J.-F.; Ferret, J. M. (Movement & Sport Sciences - Science & Motricité, 2014)
The high performance sport through regular activity, repetition of stereotypical high intensity movements and specificity of training, outlines the risk of sports injuries. Risk has increased substantially with the requirements of the highest level, the frequency of growing competition, the pressure of the result and the emergence of the sports business. Given this risk, the isokinetic registers as a reference technique in the assessment of muscle performance. The isokinetic dynamometer allows accurate and reproducible measurement of dynamic muscle strength, provided you follow a rigorous methodology. The use of isokinetic in top-level sport has grown dramatically to identify risk profiles muscle, and correct muscle imbalances, prevent injury. In treatment we use for isokinetic rehabilitation of muscle, tendon and ligament (ACL tear) diseases. Today, the eccentric muscle work must prevail in the pathologies mentioned above. The implementing rules of the protocol determine its effectiveness. We advocate for years, an early treatment of the injury by eccentric isokinetic work at slow speed in a scar purpose of injured tissue. The isokinetic tool to achieve this eccentric work early so secure. It is complementary to other physiotherapy techniques. It seems essential in the management of high-level athletes to monitor rehabilitation and full functional recovery. It quantifies one of the criteria for return to play to reduce the risk of recurrence dreaded. After anterior cruciate ligament surgery, objectify precisely the level of muscle recovery to better individualize therapy and phase réathlétisation.